Urban soundscapes in the historic centre of Thessaloniki: sonic architecture and sonic identity. Issue 2 (3rd July 2018) - Karapostoli, Aimilia; Votsi, Nefta-Eleftheria
ABSTRACT: This paper shows that contemporary sound in urban areas consists of a fragile equilibrium of sonic territories with high heterogeneity. Sound scenes in urban environments are studied using ecological sound tools, including soundscape ecology and acoustic ecology. This study proposes an interdisciplinary framework that combines quantitative and qualitative sonic and architectural data to analyse, describe and design sonic space. Five territories with distinctive sonic identities in the historic centre of Thessaloniki in Greece were selected and compared with their architectural characteristics. Though these characteristics of Thessaloniki are similar to other cities of Greece, the continuing transformation of urban sonic identities lends importance to this research. The analysis revealed unique information about the identity and urbanity of the territories, challenging the established noise–silence dichotomy and opening up new perspectives on an integrated sustainable urban design.